1978
DOI: 10.1111/j.1550-7408.1978.tb04167.x
|View full text |Cite
|
Sign up to set email alerts
|

Fine Structure of Human Malaria In Vitro*†

Abstract: The erythrocytic cycle of the human malaria parasite, Plasmodium, falciparum, was examined by electron microscopy. Three strains of parasites maintained in continuous culture in human erythrocytes were compared with in vivo infections in Aotus monkeys. The ultrastructure of P. falciparum is not altered by continuous cultivation in vitro. Mitochondria contain DNA-like filaments and some cristae at all stages of the erythrocytic life cycle. The Golgi apparatus is prominent at the schizont stage and may be involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
148
1

Year Published

1987
1987
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(153 citation statements)
references
References 35 publications
4
148
1
Order By: Relevance
“…1E), the FV. Although the relationship between the cytostome and the FV has not been empirically established, the prevailing theory is that the FV is formed from the fusion of several cytostomederived vesicles (Langreth et al, 1978). In this scenario, cytostome formation would precede FV formation.…”
Section: A New Model For Hemoglobin Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…1E), the FV. Although the relationship between the cytostome and the FV has not been empirically established, the prevailing theory is that the FV is formed from the fusion of several cytostomederived vesicles (Langreth et al, 1978). In this scenario, cytostome formation would precede FV formation.…”
Section: A New Model For Hemoglobin Transportmentioning
confidence: 99%
“…Because of the similarities between the current model for hemoglobin transport and the endocytic pathway in higher eukaryotes (Goldberg et al, 1990;Hoppe et al, 2004;Langreth et al, 1978;Saliba et al, 2003), we investigated the role of actin dynamics in hemoglobin transport to the FV. Actin has been shown to play various regulatory roles in endocytosis, including recruiting endocytic components to the plasma membrane, initiating plasma membrane invaginations, vesicle scission and transport to endocytic compartments (Kaksonen et al, 2006;Qualmann et al, 2000;Smythe and Ayscough, 2006).…”
mentioning
confidence: 99%
“…(Sinden & Smalley, 1979;Alano & Carter, 1990;Lobo & Kumar, 1998). Several lines of evidence on morphological, ultrastructural and genetic analyses of the mitochondria in P. falciparum suggest that the organelle may be functionally regulated during differentiation in the human host (Aikawa et al, 1966;Aikawa, 1971;Langreth et al, 1978;Fry & Beesley, 1991;Feagin & Drew, 1995;Petmitr & Krungkrai, 1995;Learngaramkul et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…2A). Vesicles or tubules, similar to membrane-bound structures described in schizont-infected erythrocytes (Langreth et al 1978, Atkinson & Aikawa 1990, were found within the space defined by the outermost membrane and the residual body ( Fig. 2A).…”
Section: Resultsmentioning
confidence: 92%
“…The fact that these structures are not detectable on schizontinfected erythrocytes either by transmission (Langreth et al 1978, Atkinson & Aikawa 1990 or SEM (Gruenberg et al 1983), suggests that the formation of such membrane modifications might be functionally related to the release of merozoites from infected erythrocytes.…”
Section: Discussionmentioning
confidence: 99%